Math
/
Natural Logarithm

Natural Logarithm

Shiken premium Upgrade Banner

Exploring the Basics of Natural Logarithms

Natural logarithms, represented by ln, are a specific type of logarithm with the base of e (2.71828...). The notation for natural logarithms is ln(x), which can also be expressed as ex. Having a thorough understanding of how to convert between natural logarithms and exponential functions is fundamental in tackling equations and simplifying expressions.

Converting between Natural Logarithms and Exponential Functions

To convert a natural logarithm into exponential form, follow these steps:

  • Identify e as the base, y as the exponent, and x as the result of the exponential form
  • Rewrite the equation as ey=x

To convert from exponential to logarithmic form, assign e as the base, x as the exponent, and 5 as the result of the exponential. This can be expressed as ln(5)=x.

Rules Governing Natural Logarithms

In addition to specific rules for natural logarithms, the general laws of logs and exponential rules can also be applied. This provides a comprehensive toolkit for solving equations and simplifying expressions involving natural logarithms.

Proving the Rules of Natural Logarithms

To demonstrate the validity of natural logarithm rules, it is necessary to understand each step of the process. A similar approach can be adopted as in proving laws of logs. For instance, showing that Ln(1)=0 can be done by rewriting it as em=1 and applying the power=0 exponential law, which yields m=0. This ultimately proves that Ln(1)=0 is equivalent to e0=1.

Similarly, the proof of ln(e)=1 relies on the fact that exponential and logarithmic functions are inverses of each other. Hence, Ln(e) will cancel out, leaving 1 as the solution.

To prove that Ln(y)=Ln(x) implies y=x, let Ln(y)=a and Ln(x)=b, and then convert each function into an exponential form. This will result in ea=y and eb=x. Since Ln(y)=Ln(x), it follows that a=b, proving that y=x.

Practical Applications of Natural Logarithms

Example 1: Solve 6=e2x. Rewrite this in logarithmic form as Ln(6)=2x, where e is the base, 2x is the exponent, and 6 is the result of the exponential.

Example 2: Solve 10=ex+3. Convert this into logarithmic form as Ln(10)=x+3, where e is the base, x+3 is the exponent, and 10 is the answer of the exponential.

Example 3: Solve e=ex. Since exponential and logarithm functions are inverses, e and Ln will cancel out, giving x=1 as the solution.

Example 4: Solve 2.4=e1.4x. To obtain x on its own, rewrite this in logarithmic form as Ln(2.4)=1.4x. Thus, x=Ln(2.4)/1.4.

Example 5: Solve Ln(4)=Ln(2)+Ln(2). Applying the power rule, this can be rewritten as Ln(4)=Ln(22). This simplifies to Ln(4)=2Ln(2).

Key Takeaways from Natural Logarithms

  • Natural logarithms utilize e as the base.
  • The rules governing natural logarithms, combined with the general laws of logs and exponentials, enable us to solve equations and simplify expressions.
  • A thorough comprehension of the relationship between natural logarithms and exponential functions is crucial in advanced mathematics and sciences.

In Conclusion

Natural logarithms are a powerful tool in solving equations and simplifying expressions with a base of e. By mastering the rules and conversion between exponential and logarithmic forms, we can effectively apply natural logarithms in various mathematical and scientific scenarios.

Explore More Subject Explanations

Try Shiken Premium
for Free

14-day free trial. Cancel anytime.
Get Started
Join 20,000+ learners worldwide.
The first 14 days are on us
96% of learners report x2 faster learning
Free hands-on onboarding & support
Cancel Anytime